PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA APARTEMEN SERPONG M TOWN SIGNATURE - Roma Dhona Hadisuryo, Alamuda; Sari, Ratna (Journal of Research and Publication Innovation, 2024)
influence between work discipline and the work environment, either partially or simultaneously, on employee performance at the Serpong M Town Signature Apartment. This research uses descriptive quantitative research methods. The sampling technique used saturated sampling / Slovin's formula and a sample of 65 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of the research show that work discipline has a positive effect on employee performance at the Serpong M Town Signature Apartment with a regression equation of Y = 3.119 + 0.367 ), this hall is also proven with a significance of 0.001 < 0.05, so it is said that Ho is rejected and Ha means that work discipline has a significant effect on employee performance at the Serpong M Town Signature Apartment. The work environment has a positive effect on employee performance with a regression equation of Y = 3.119 + 0.573 X2. The coefficient of determination is 21.8% and the hypothesis test is obtained t table> t table ttalbel (5,325> 1,998), this hall Regarding the operational environmental performance of the Serpong M Town Signalture Airport, there is a significant influence. Work discipline and work environment simultaneously have a positive effect on employee performance with the regression equation Y = 3.119 + 0.573 + 0.367, the correlation coefficient is 0.888 in the sig value. F challenge of 0.000, total < 0.05 malkal valrialbel work discipline (X1) in the work environment (X2) has a very strong level of influence. The coefficient of determination value was 78.9%, while the remaining 21.1% of the signal was influenced by other traffic signal factors which were not studied. Hypothesis testing obtained a calculated F value > F table or (115.787 > 3.14), this was also confirmed by Sig < 0.05 plus (0.000 < 0.05). In this way, Ho3 is rejected and Hal3 is accepted, this shows that there is a significant simultaneous influence on work discipline and work environment in the work environment on the performance of traffic on the Serpong M Town Signal Tower Alpalrtemen.